Polyanionic cellulose for petroleum drilling and preparation method thereof
By designing molecular structures and using inorganic-organic hybrid technology, a three-dimensional hybrid structure of cellulose-molecular sieve was constructed, which solved the problem of performance degradation of polyanionic cellulose under high temperature and high salt conditions, and achieved efficient filtration loss control and thickening effect under high temperature and high salt conditions.
Patent Information
- Application Number
- CN202511766949.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-28
- Publication Date
- 2025-12-26
AI Technical Summary
Existing polyanionic cellulose exhibits a sharp decline in performance under high temperature and high salinity conditions, making it difficult to meet the high-performance requirements of deep and ultra-deep well drilling.
By employing molecular structure design and inorganic-organic hybrid technology, a three-dimensional hybrid structure of cellulose-molecular sieve is constructed through silane grafting and in-situ growth of NaA-type molecular sieves, thereby enhancing viscosity stability and filtration loss control capabilities.
It maintains a viscosity of over 80% at 180℃ and in saturated brine, with an API filtration loss of ≤10mL, significantly improving the product's performance in extreme environments.
Smart Images

Figure CN121203631A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polyanionic cellulose preparation technology, specifically relating to a polyanionic cellulose for oil drilling and its preparation method. Background Technology
[0002] Polyanionic cellulose (PAC), as an important water-soluble cellulose ether, is widely used as a filtration reducer and viscosity enhancer in water-based drilling fluids due to its excellent thickening, suspending, and colloidal protection properties. Its mechanism of action mainly relies on the hydration of anionic groups such as carboxymethyl groups on the molecular chain. By forming an adsorbed hydration layer on the surface of clay particles and increasing the viscosity of the liquid phase, it effectively controls filtration loss and maintains wellbore stability.
[0003] However, during deep and ultra-deep well drilling, the harsh environment of high downhole temperatures (often exceeding 150°C) and high mineralization (such as saturated brine and high calcium and magnesium ion content) poses a severe challenge to traditional PAC (Polymerized Acid Carboxymethyl Alkali). High temperatures trigger the hydrolysis of surface carboxymethyl groups and oxidative degradation of molecular chains, while high concentrations of salt ions severely compress the diffused double layer around the molecular chains, inhibiting the hydration of anionic groups. This leads to a sharp decrease in the viscosity of the PAC solution and a significant decline in its filtration control capability. Ordinary PAC products often struggle to maintain effective performance in temperatures exceeding 150°C or in saturated brine, limiting their application under complex geological conditions.
[0004] To improve the temperature and salt resistance of polyacrylamide (PAC), existing technologies mainly focus on chemical modification and process optimization. For example, a two-stage alkalization and etherification process (CN101003577B) is used to improve the degree of substitution and uniformity; a crosslinking agent (CN101838334A) is introduced to enhance the rigidity of the molecular chain; or a composite solvent system is used to improve reaction efficiency. Although these methods improve the performance of PAC to some extent, their effects are mostly limited to adjustments within the organic molecular structure and have not yet overcome the fundamental limitations of easy degradation of polymer chains under extreme conditions and easy compression of the hydration layer. When faced with the dual stresses of high temperature (above 180℃) and high salt, existing modified PAC still suffers from insufficient performance retention and unstable control of filtration loss.
[0005] Therefore, there is an urgent need in this field for an innovative technical solution that can go beyond the existing framework of organic modification and fundamentally enhance the structural stability and hydration performance of PAC in ultra-high temperature and high mineralization environments, so as to meet the urgent demand of modern deep well and complex formation drilling for high-performance treatment agents. Summary of the Invention
[0006] To address the common technical challenge of rapid performance degradation of polyanionic cellulose under high-temperature and high-salt environments in existing technologies, this invention aims to provide a polyanionic cellulose for oil drilling and its preparation method. This method, through an innovative combination of molecular structure design and inorganic-organic hybrid technology, aims to significantly improve the viscosity stability and filtration loss control of the product under harsh conditions such as temperatures above 180°C and saturated brine. To solve the above-mentioned technical problems, this invention adopts the following technical solution: This invention provides a method for preparing polyanionic cellulose for oil drilling, the method comprising the following steps: S1 cellulose activation: Place bleached wood pulp or cotton pulp cellulose in a 1-3 wt% NaOH aqueous solution, stir and soak at 20-40℃ for 1-3 hours, then filter, wash with water until neutral, then acidify with 0.05-0.2 mol / L organic or inorganic acid for 5-15 minutes, wash again with water, replace water with ethanol, and vacuum dry at 60-80℃ to obtain activated cellulose; S2 Silane Grafting: The activated cellulose obtained in step S1 is dispersed in an alcohol-water mixed solvent with a mass ratio of alcohol to water of 85-95:5-15. The pH of the system is adjusted to 4.5-5.5 using a pH adjuster. Under nitrogen or inert gas protection, N-β-aminoethyl-γ-aminopropyltrimethoxysilane KH-792 is added dropwise. The amount of KH-792 is 20-40% of the dry weight of the activated cellulose. The reaction is refluxed at 40-60℃ for 2-6 hours. After the reaction is completed, the mixture is cooled, filtered, washed with alcohol, and dried to obtain aminated cellulose. S3 In-situ growth of NaA-type molecular sieves: The aminated cellulose obtained in step S2 is placed in a Na2O-Al2O3-SiO2-H2O sol system. The molar composition of the sol is (2.8-3.5)Na2O:1.0Al2O3:(1.8-2.2)SiO2:(120-150)H2O, and the mass ratio of aminated cellulose to sol is 1:(15-30). The temperature is raised to 60-120℃ in a closed microwave reactor by microwave heating, and the reaction is kept at a constant temperature for 15-120 min. After cooling, the mixture is filtered, washed, and dried to obtain a cellulose-NaA molecular sieve hybrid. S4 Post-processing: The hybrid material from step S3 is crushed and sieved to obtain a finished polyanionic cellulose product for oil drilling with a particle size ≤0.18mm.
[0007] Further, the organic acid in step S1 is acetic acid or citric acid, and the inorganic acid is hydrochloric acid or sulfuric acid; the acidification time is 5-15 min, and the conductivity after acidification is ≤200 μS·cm. -1 .
[0008] Further, in step S2, the alcohol-water mixed solvent is ethanol-water or isopropanol-water; the pH adjuster is selected from acetic acid, citric acid or dilute hydrochloric acid; the reaction temperature is 45-55℃, and the reaction time is 3-5h.
[0009] Furthermore, the sol described in step S3 is first aged at 20-40℃ for 12-48 hours before being added to aminated cellulose; the microwave heating power is 300-600W, and the heating rate is 3-8℃ / min.
[0010] Furthermore, the mass fraction of the NaA-type molecular sieve obtained in step S3 in the hybrid is 15-30%.
[0011] Furthermore, step S4 is followed by an ion exchange step: the product is placed in a 0.3-0.8 mol / L CaCl2 or MgCl2 solution, stirred at 25-50°C for 30-120 min, filtered, washed with water, and dried to obtain Ca... 2+ or Mg 2+ Polyanionic cellulose.
[0012] Furthermore, the polyanionic cellulose for oil drilling: Moisture ≤8wt%; When 1 wt% of finished polyanionic cellulose for oil drilling is added to saturated brine, the apparent viscosity is ≥45 mPa·s. ; Viscosity retention rate ≥80% after hot rolling aging at 180℃ for 16 hours; API filtration loss ≤10mL (180℃, 3.5MPa, 1wt% dosage).
[0013] Furthermore, polyanionic cellulose is used as a filtration reducer and viscosity enhancer in deep and ultra-deep well drilling fluids.
[0014] The significant performance improvement of the inorganic-organic hybrid polyanionic cellulose (PAC) prepared by this invention stems from its unique "three-dimensional composite structure" and the resulting "multifunctional synergistic effect." Firstly, its superior thickening effect originates from the physical cross-linking network constructed between the rigid molecular sieve nanoparticles and the flexible polymer chains. Through silane coupling and in-situ hydrothermal synthesis, the NaA-type molecular sieve is firmly anchored to the cellulose backbone, and its abundant silanol groups (≡Si–OH) on its surface interact with the carboxyl groups on the PAC chains. The formation of numerous hydrogen bonds and coordination bonds makes the molecular sieve a robust "deformable cross-linking point." This structure forms a three-dimensional "cellulose-molecular sieve" framework that runs through the entire system in aqueous solution, greatly enhancing the structural resistance to fluid flow, thus macroscopically exhibiting a significant increase in apparent viscosity and elastic modulus at the same concentration and shear.
[0015] Furthermore, this hybrid structure, through a triple synergistic mechanism of ion fixation, thermal management, and moisture slow release, endows the product with excellent salt resistance and heat resistance.
[0016] Salt tolerance: The regular 0.41 nm pores of NaA molecular sieve can selectively adsorb and immobilize hydrated Na. + With Ca 2+ This process converts free salt ions into lattice-fixed ions, effectively reducing the solution conductivity and weakening the charge shielding effect on the PAC chains, allowing them to maintain their extended conformation in salt water.
[0017] Heat resistance: The inorganic phase of molecular sieve has both higher thermal conductivity and Brønsted acid sites, which can quickly disperse local thermal stress and capture alkoxy free radicals that cause chain breakage, thereby inhibiting high-temperature degradation.
[0018] Hydration maintenance: The high specific surface area of molecular sieves can adsorb a large amount of bound water, which is slowly released at high temperature to maintain the hydration layer of PAC and delay dehydration and curling.
[0019] Ultimately, the synergistic effect of these multiple mechanisms ensures that the product maintains stable rheological and filtration control performance even under harsh environments with high salt and high temperature.
[0020] Compared with the prior art, the present invention has the following significant advantages: The product has a high temperature resistance limit; after hot rolling aging at 180℃ for 16 hours, the viscosity retention rate is ≥80%. It exhibits excellent salt resistance and maintains good viscosity-enhancing and filtration loss-reducing effects even in saturated brine drilling fluid, with an API filtration loss of ≤10 mL. Combining the flexibility of organic materials with the thermal stability of inorganic materials, the product's overall performance surpasses that of traditional PAC and single-modification products, making it particularly suitable for drilling in deep wells, ultra-deep wells, and complex formations. Attached Figure Description
[0021] Figure 1 A schematic diagram of a process for preparing polyanionic cellulose for oil drilling; Figure 2 XRD pattern of composite material P-1 prepared in Example 1. Detailed Implementation
[0022] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below in conjunction with the embodiments of this invention. Obviously, the described embodiments are only a part of the embodiments of this invention, not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.
[0023] The following examples illustrate a polyanionic cellulose for oil drilling and its preparation method provided by the present invention.
[0024] Example 1:
[0025] S1 cellulose activation Weigh 20.0 g of bleached softwood pulp (degree of polymerization ~800), shred it, and place it in 400 mL of 2 wt% NaOH aqueous solution. Stir mechanically at 30 °C for 2 hours. Filter and wash repeatedly with deionized water until the filtrate is neutral. Transfer the cellulose to 200 mL of 0.1 mol / L acetic acid solution and acidify at room temperature for 10 minutes. Filter again and wash with deionized water until the conductivity of the filtrate is 180 µS·cm⁻¹. Displace the cellulose with 200 mL of anhydrous ethanol three times, and finally dry in a vacuum drying oven at 70 °C for 12 hours to obtain activated cellulose (AC).
[0026] S2 silane grafting In a 500 mL three-necked flask, add 10.0 g AC, 171 g anhydrous ethanol, and 19 g deionized water, and mechanically stir to disperse them evenly. Adjust the pH of the system to 5.0 by adding glacial acetic acid dropwise. Under nitrogen protection, slowly add 3.0 g KH-792. Reflux the reaction in an oil bath at 50 °C for 4 hours. After the reaction is complete, cool to room temperature, filter, and wash the solid three times with 150 mL anhydrous ethanol. Dry the solid under vacuum at 80 °C for 8 hours to obtain aminated cellulose.
[0027] S3 In-situ Growth of NaA Type Molecular Sieves Sol preparation: Solution A: Dissolve 2.46 g NaAlO2 and 3.00 g NaOH in 40 g deionized water and stir until clear. Solution B: Dissolve 6.22 g Na2SiO3·9H2O in 40 g deionized water. Under vigorous stirring, quickly pour Solution A into Solution B. The mixture is then aged at 30°C with continuous stirring for 24 hours to obtain a homogeneous sol.
[0028] Hydrothermal synthesis: 2.0 g of aminated cellulose was weighed and completely impregnated in 40 g of the above sol. The mixture was transferred to a 100 mL microwave reactor, with a filling degree of 70%. The reactor was placed in a microwave hydrothermal synthesizer, and the program was set to heat to 80 °C at a rate of 5 °C / min and then hold at 100 °C for 30 minutes. After natural cooling, the solid was collected by vacuum filtration, washed twice with 0.1 M NaCl solution, and then washed with deionized water until the pH of the filtrate was 9. The filtrate was then vacuum dried at 60 °C for 12 hours to obtain the cellulose-NaA molecular sieve composite material. The molecular sieve loading was calculated to be approximately 22%.
[0029] S4 Post-processing The obtained cellulose-NaA molecular sieve composite material was pulverized using a small pulverizer and passed through an 80-mesh standard sieve (0.18 mm aperture) to obtain the final product P-1.
[0030] like Figure 1 As shown, the obtained composite material P-1 was characterized by X-ray diffraction (XRD). Its XRD pattern showed obvious diffraction peaks at 2θ = 7.18°, 10.16°, 12.45°, 16.10°, 21.64°, 23.98°, 27.10°, 29.86°, and 34.10°. These diffraction peaks correspond to the (200), (220), (222), (420), (422), (600), (622), (642), and (644) crystal planes characteristic of standard NaA-type molecular sieves (LTA type, JCPDS PDF card number 00-039-0222), respectively. The positions and relative intensities of all characteristic peaks correspond to the above standard card patterns. Only sharp diffraction peaks of the NaA molecular sieve were observed in the pattern, while the typical broad diffuse diffraction signal of the cellulose matrix was not detected. This indicates that, despite the molecular sieve loading of approximately 22%, the strong diffraction effect generated by its highly ordered crystal structure completely masked the weak diffraction signal of the underlying cellulose, thus confirming the successful synthesis of the highly crystalline NaA molecular sieve in the product.
[0031] Example 2:
[0032] The difference from Example 1 lies in the hydrothermal reaction conditions in step S3: microwave heating to 110°C and constant temperature reaction for 45 minutes. The remaining steps and parameters are exactly the same as in Example 1, yielding product P-2.
[0033] Example 3:
[0034] Based on the product P-1 obtained in Example 1, ion exchange was performed: 5.0 g of P-1 was weighed and dispersed in 100 mL of 0.5 mol / L CaCl2 solution, and stirred at 40°C for 1 hour. The mixture was then filtered, washed with deionized water until no chloride ions were detected (the filtrate showed no white precipitate when tested with 0.1 M AgNO3 solution), and dried under vacuum at 60°C to obtain the Ca²⁺ type product P-3-Ca.
[0035] Comparative Example 1: Polyanionic cellulose was prepared using a traditional one-step alkalization-etherification process: 10g of refined cotton was mixed with isopropanol solvent, sodium hydroxide was added for alkalization, followed by the addition of chloroacetic acid for etherification, and then neutralized, washed, and dried to obtain the traditional PAC product C-1.
[0036] Performance testing: The performance of the prepared products P-1, P-2, P-3-Ca and comparative example C-1 was tested, and the results are as follows: Note: The apparent viscosity of 1% saturated brine is calculated by adding 1% by weight of this product to saturated brine and measuring the viscosity using a rheometer at room temperature (25°C) for 170 seconds. -1 Tested at shear rate The viscosity of the sample after hot rolling at 180℃ for 16 hours was determined by dynamically rolling the sample in a roller heating furnace at a high temperature of 180℃ for 16 hours after the apparent viscosity test of the 1% saturated salt water was measured. The sample was then removed, cooled to room temperature, and the viscosity of the solution was measured.
[0037] Table 1 Performance Tests of Products Prepared in Examples and Comparative Examples
[0038] Test data shows that the polyanionic cellulose (P-1, P-2, P-3-Ca) for oil drilling prepared in this invention all meet the high-performance indicators. Especially in terms of high-temperature aging resistance and high-temperature, high-pressure filtration loss control, it is significantly superior to products produced by traditional processes. This fully demonstrates that the synergistic effect of silane grafting and in-situ composite with NaA molecular sieves can greatly improve the application performance of polyanionic cellulose under extreme working conditions.
Claims
1. A method for preparing polyanionic cellulose for oil drilling, characterized in that, The method includes the following steps in sequence: S1 cellulose activation: Place bleached wood pulp or cotton pulp cellulose in a 1-3 wt% NaOH aqueous solution, stir and soak at 20-40℃ for 1-3 hours, then filter, wash with water until neutral, then acidify with 0.05-0.2 mol / L organic or inorganic acid for 5-15 minutes, wash again with water, replace water with ethanol, and vacuum dry at 60-80℃ to obtain activated cellulose; S2 Silane Grafting: The activated cellulose obtained in step S1 is dispersed in an alcohol-water mixed solvent with a mass ratio of alcohol to water of 85-95:5-15. The pH of the system is adjusted to 4.5-5.5 using a pH adjuster. Under nitrogen or inert gas protection, N-β-aminoethyl-γ-aminopropyltrimethoxysilane KH-792 is added dropwise. The amount of KH-792 is 20-40% of the dry weight of the activated cellulose. The reaction is refluxed at 40-60℃ for 2-6 hours. After the reaction is completed, the mixture is cooled, filtered, washed with alcohol, and dried to obtain aminated cellulose. S3 In-situ growth of NaA-type molecular sieves: The aminated cellulose obtained in step S2 is placed in a Na2O-Al2O3-SiO2-H2O sol system. The molar composition of the sol is (2.8-3.5)Na2O:1.0Al2O3:(1.8-2.2)SiO2:(120-150)H2O, and the mass ratio of aminated cellulose to sol is 1:(15-30). The temperature is raised to 60-120℃ in a closed microwave reactor by microwave heating, and the reaction is kept at a constant temperature for 15-120 min. After cooling, the mixture is filtered, washed, and dried to obtain a cellulose-NaA molecular sieve hybrid. S4 Post-processing: The hybrid material from step S3 is crushed and sieved to obtain a finished polyanionic cellulose product for oil drilling with a particle size ≤0.18mm.
2. The method for preparing polyanionic cellulose for oil drilling according to claim 1, characterized in that, In step S1, the organic acid is acetic acid or citric acid, and the inorganic acid is hydrochloric acid or sulfuric acid; the acidification time is 5-15 min, and the conductivity after acidification is ≤200 μS·cm. -1 .
3. The method for preparing polyanionic cellulose for oil drilling according to claim 1, characterized in that, In step S2, the alcohol-water mixed solvent is ethanol-water or isopropanol-water; the pH adjuster is selected from acetic acid, citric acid or dilute hydrochloric acid; the reaction temperature is 45-55℃ and the reaction time is 3-5h.
4. The method for preparing polyanionic cellulose for oil drilling according to claim 1, characterized in that, In step S3, the sol is first aged at 20-40℃ for 12-48 hours, and then aminated cellulose is added; the microwave heating power is 300-600W, and the heating rate is 3-8℃ / min.
5. The method for preparing polyanionic cellulose for oil drilling according to claim 1, characterized in that, The mass fraction of the NaA-type molecular sieve obtained in step S3 in the hybrid is 15-30%.
6. The method for preparing polyanionic cellulose for oil drilling according to claim 1, characterized in that, The process includes an ion exchange step after step S4: the finished product is placed in a 0.3-0.8 mol / L CaCl2 or MgCl2 solution, stirred at 25-50℃ for 30-120 min, filtered, washed with water, and dried to obtain Ca or Mg type polyanionic cellulose.
7. A polyanionic cellulose for oil drilling according to any one of claims 1-6, characterized in that, The performance indicators of the finished polyanionic cellulose product for oil drilling are as follows: Moisture ≤8wt%; When 1 wt% of finished polyanionic cellulose for oil drilling is added to saturated brine, the apparent viscosity is ≥45 mPa·s, and the test condition is 170 s. -1 25℃; Viscosity retention rate ≥80% after hot rolling aging at 180℃ for 16 hours; API filtration loss ≤10mL, test conditions 180℃, 3.5MPa, 1wt% dosage.
8. The polyanionic cellulose for oil drilling according to claim 7, characterized in that, The polyanionic cellulose for oil drilling is suitable for use in deep or ultra-deep well drilling fluids to simultaneously reduce drilling fluid filtration loss and increase its viscosity.
Citation Information
Patent Citations
Technique for producing polyanionic cellulose with high degree of substitution
CN101003577B
Preparation method of high viscosity polyanion cellulose
CN101838334A
Cellulose derivative-silicon-based hybrid microsphere and preparation method thereof
CN113908813A
Method for preparing hierarchical pore molecular sieve through regulation and control of electrostatic spinning nanocellulose
CN114956113A
Preparation method of hierarchical pore A type molecular sieve regulated and controlled by nanocellulose
CN115140744A